2023
DOI: 10.1021/acsenergylett.3c02586
|View full text |Cite
|
Sign up to set email alerts
|

Can ChatGPT and Other AI Bots Serve as Peer Reviewers?

Jillian M. Buriak,
Mark C. Hersam,
Prashant V. Kamat

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information T he recent emergence of artificial intelligence (AI) bots, such as ChatGPT, Bing AI Chat and Copilot (Microsoft), and Bard (Google), has led the scientific community to explore the capabilities of Large Language Models (LLMs) in scientific research. 1 Recently, several editorials, articles, and blog posts have appeared discussing the pros and cons of using such AI bots in scientific publications. 2−6 On the positive side, these tools are useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These discussions have been fueled by the emergence of sophisticated artificial intelligence models, such as ChatGPT, based on the generative pre-trained transformer (GPT) architecture [36]. These models, including ChatGPT, have been extensively discussed and explored in various fields, such as scientific research, orthopedic surgery, pathology, academic writing, healthcare, and environmental health research [36][37][38][39][40][41][42]. The paradigm shift in AI, marked by the development of models like BERT, DALL-E, and GPT-3, has further intensified the discourse on the capabilities and limitations of these large language models [43].…”
Section: When Ai Goes Awry: Understanding the Risks Of Unpredictable ...mentioning
confidence: 99%
“…These discussions have been fueled by the emergence of sophisticated artificial intelligence models, such as ChatGPT, based on the generative pre-trained transformer (GPT) architecture [36]. These models, including ChatGPT, have been extensively discussed and explored in various fields, such as scientific research, orthopedic surgery, pathology, academic writing, healthcare, and environmental health research [36][37][38][39][40][41][42]. The paradigm shift in AI, marked by the development of models like BERT, DALL-E, and GPT-3, has further intensified the discourse on the capabilities and limitations of these large language models [43].…”
Section: When Ai Goes Awry: Understanding the Risks Of Unpredictable ...mentioning
confidence: 99%
“…The terms AI and ChatGPT have grown more and more synonymous over the past year. There are various applications of AI bots in journalism and media education, scientific applications like peer reviews, drug discovery, material design, or even scientific discovery itself . In education, initial research on using generative AI mainly revolved around strengths and weaknesses and opportunities and challenges. , Scholars extensively tested what potential ChatGPT has in the educational context by evaluating answers given by the generative AI and proposed a range of applications in several fields of education. This same development was seen in chemistry education, where scientists evaluated academic answers given by AI, describing mixed performances by ChatGPT in terms of application of knowledge. , They compared AI-generated answers to student answers and found that the AI was sound in some areas but made mathematical mistakes that students would not make .…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of AI tools, such as Large Language Models (referred as LLMs), has now raised a new dilemma. , Since any phrases or paragraphs can be rewritten either with built-in tools in word processing software or with AI tools such as ChatGPT or Bing, , it becomes difficult to identify sentences between the original work versus copied work. One such example of a paragraph that was revised by ChatGPT is presented in Figure . As expected, ChatGPT has inserted synonyms or changed the structure of the sentence without altering the meaning of the sentences.…”
mentioning
confidence: 99%
“…An example to show how ChatGPT 3.5 can rewrite a paragraph that is unlikely to be flagged for plagiarized sentences, thus avoiding plagiarism check. The paragraph was selected from an earlier editorial (from ref , Copyright 2024 American Chemical Society).…”
mentioning
confidence: 99%